Implementation of Clean and Healthy Living Behaviors among Households in the Service Area of Pattalassang Health Center, Gowa District - Muhammad Ilyas; Muhammad Syafar; Rahmawati Azis (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
This research aims to analyze the implementation of Clean and Healthy Living Behavior (PHBS) in households in the work area of the Patalassang Community Health Center, Gowa Regency. This research aimed to examine the encouraging and inhibiting factors for household PHBS implementation. The research was carried out using in-depth interviews and observations of informants who manage PHBS at the community health center level, as well as housewives and community leaders and assisted with data analysis software called MAXQDA which was used to explore the factors driving and inhibiting the implementation of PHBS through in-depth interviews, focus group discussions, and observation. The research results showed that adequate knowledge about PHBS, social support, both from family, community health centers and the government, as well as educational programs run by community health centers are the main driving factors. On the other hand, lack of knowledge, low personal awareness, and limited facilities such as sanitation, clean water and proper toilets are significant obstacles in implementing PHBS. The conclusions of this research emphasize the importance of increasing health education, strengthening social support, providing adequate sanitation facilities, and increasing individual awareness and motivation to achieve optimal PHBS implementation. With an integrated and collaborative approach, it is hoped that the implementation of PHBS in households in the Patalassang Community Health Center working area can continue to be improved, thus contributing to improving the overall quality of community health.